Engineering and Economic Evaluation Perspective in the Production of NiO Nanoparticles - Friska Apriliana; Asep Bayu Dani Nandiyanto (Universitas Ahmad Dahlan, 2019)
Nickel oxide (NiO) nanoparticles have been proven and can be used in a variety of important applications. The purpose of this research was to evaluate the production process of NiO nanoparticles using the industrial co-precipitation method in terms of engineering and economic evaluation. Specifically, research was conducted by varying raw materials, product selling prices (GPM), equipment prices, and number of employees, which are compared with several economic parameters such as total investment cost (TIC), gross profit margin (GPM), break even point (BEP), payback period (PBP), net present value (NPV), and cumulative net present value (CNPV). The results showed that the PBP analysis showed that the investment would be profitable after more than 4 years with minimum product sales (GPM) of at least 90% and an increase in the price of raw materials no more than 15% of the ideal price. From this economic evaluation analysis, we can conclude that this project is feasible to run.